2023
DOI: 10.1186/s12967-023-04171-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of immune-related secretory proteins linking chronic kidney disease with calcific aortic valve disease based on comprehensive bioinformatics analysis and machine learning

Abstract: Background Chronic kidney disease (CKD) is one of the most significant cardiovascular risk factors, playing vital roles in various cardiovascular diseases such as calcific aortic valve disease (CAVD). We aim to explore the CKD-associated genes potentially involving CAVD pathogenesis, and to discover candidate biomarkers for the diagnosis of CKD with CAVD. Methods Three CAVD, one CKD-PBMC and one CKD-Kidney datasets of expression profiles were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Transcriptome overlap analysis is a genetic validation method for analyzing the relationship between two diseases. For example, based on three datasets of polycystic ovary syndrome and recurrent implantation failure, 12 disease overlapping genes were identified using weighted gene co expression networks, functional enrichment analysis, and three machine learning algorithms, which potential pathogenic associations and mechanisms between the two were explored [ 28 ]; The inflammatory immune pathway of calcified aortic valve disease (CAVD) related to chronic kidney disease (CKD) had been revealed, providing new insights for future serum based diagnosis and treatment interventions for CKD combined with CAVD [ 29 ]. In this study, 418 upregulated overlapping genes were identified using the GEO dataset of SLE and PBC, and their biological functions were found to be related to TNF signaling pathway and JAK-STAT signaling pathway, which was similar to previous reports [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome overlap analysis is a genetic validation method for analyzing the relationship between two diseases. For example, based on three datasets of polycystic ovary syndrome and recurrent implantation failure, 12 disease overlapping genes were identified using weighted gene co expression networks, functional enrichment analysis, and three machine learning algorithms, which potential pathogenic associations and mechanisms between the two were explored [ 28 ]; The inflammatory immune pathway of calcified aortic valve disease (CAVD) related to chronic kidney disease (CKD) had been revealed, providing new insights for future serum based diagnosis and treatment interventions for CKD combined with CAVD [ 29 ]. In this study, 418 upregulated overlapping genes were identified using the GEO dataset of SLE and PBC, and their biological functions were found to be related to TNF signaling pathway and JAK-STAT signaling pathway, which was similar to previous reports [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the limma package is utilized to analyze the differential expression matrix comparing the control group and DFU. To identify genes related to immune infiltration in DFU patients, we employ the criteria of |log FC| > 1 and an adjusted p-value < 0.05 16 as thresholds for detecting differentially expressed genes (DEGs).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, gene correlation networks have been widely constructed to extensively understand the mechanism underlying the high-throughput sequencing data [3]. Weighted gene coexpression network analysis (WGCNA) was a common gene correlation analysis method [4], which supplied complete interpretation into the detail of molecular interactions [5][6][7][8]. In this study, RNA sequencing datasets referred to kidney IRI were collected from the Gene Expression Omnibus (GEO) database.…”
Section: Introductionmentioning
confidence: 99%